Boy-crazy Stacey - Martin, Ann M., 1955- (New York : Scholastic, 1987)
While Stacey nurses a crush on a lifeguard much too old for her, Mary Anne is doing the work of two babysitters and she does not like it one bit!
4.0
3-6
Keywords: Babysitters -- Fiction; Babysitters -- Fiction